Fundamental Principles in Traffic Flow Modelling - Šimáně, Čestmír (2010)
Research workers started to investigate traffic flows already in thirtieth years of twentieth century. But it is true that in these times was minimal the number of vehicles on roads. However, at the end of fifties this number started to increase. So according to this it was necessary to find sophistry tools to their monitoring. More engineers interested in the theory of traffic flow and they started to describe interactions between vehicles through new theories and models. Nowadays, this work continues, because the number of vehicles on roads is still increasing. The aim of this thesis is to make reader understood the basic terms, quantities, approaches and models in theory of traffic flow.